2013
DOI: 10.1186/1471-2288-13-89
|View full text |Cite
|
Sign up to set email alerts
|

Piecewise exponential models to assess the influence of job-specific experience on the hazard of acute injury for hourly factory workers

Abstract: BackgroundAn inverse relationship between experience and risk of injury has been observed in many occupations. Due to statistical challenges, however, it has been difficult to characterize the role of experience on the hazard of injury. In particular, because the time observed up to injury is equivalent to the amount of experience accumulated, the baseline hazard of injury becomes the main parameter of interest, excluding Cox proportional hazards models as applicable methods for consideration.MethodsUsing a da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…Further, as the hazard of injury decreases after 1 year on the job,19 we adjusted for more than 1 year of experience as a potential confounder.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, as the hazard of injury decreases after 1 year on the job,19 we adjusted for more than 1 year of experience as a potential confounder.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we employed a two-piece exponential hazard with a change of hazard at 12 months (complication 3). Two-piece exponential models are a special case of the Cox PH model; our model assumes a constant baseline hazard from 0–12 months on the job, and a separate constant baseline hazard from 12 months onward 19 26. Therefore, the final model was an AG model with a piecewise exponential baseline hazard, including a frailty term at the employee level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most study groups were general samples of the working population. Four of the studies used a population of blue-collar workers (14)(15)(16)(17) and two of the studies used populations based on health care workers (18,19). The exposure measurements came either from corporate administrations (eg, payrolls), national statistics registers, or were self-reported.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Only one study examined differences in distribution between fatal and non-fatal injuries, and no difference was found between temporary and permanent workers (26). Two studies of aluminum plant workers found that unionization was associated with a higher risk of occupational injuries (17,27). Figure 2 shows a summarization of the results and effect sizes of the 17 included studies, sorted by exposures researched.…”
Section: Dimensions Of Precarious Employment Studied and Their Associmentioning
confidence: 99%